2018
DOI: 10.3390/molecules23081975
|View full text |Cite
|
Sign up to set email alerts
|

Stability Study and Identification of Degradation Products of Caffeoylgluconic Acid Derivatives from Fructus Euodiae

Abstract: Caffeoylgluconic acid derivatives are characteristic constituents isolated from the aqueous extract of Fructus Euodiae. In this research focusing on caffeoylgluconic acid derivatives, trans-caffeoyl-6-O-d-gluconic acid (CGA), trans-caffeoyl-6-O-d-gluconic acid methyl ester (CGA-ME), and trans-caffeoyl-6-O-d-glucono-γ-lactone (CGA-LT), a systematic study of stability was performed under different temperatures and pH levels by ultra performance liquid chromatography-diode array detector (UPLC-DAD) and ultra perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…We suspected that the decreased choline levels could be correlated with the purity of the product produced through extraction and fermentation. A previous study showed that pure caffeoylgluconic acid has better quality and stability than its mixture product [20].…”
Section: Discussionmentioning
confidence: 99%
“…We suspected that the decreased choline levels could be correlated with the purity of the product produced through extraction and fermentation. A previous study showed that pure caffeoylgluconic acid has better quality and stability than its mixture product [20].…”
Section: Discussionmentioning
confidence: 99%
“…Fortunately, under the guidance of the Q-Marker theory proposed by Academician Changxiao Liu, it sheds the light for the quality control of CMM related preparations with the complicated compounds ( Liu et al, 2016 , Liu et al, 2017 , Liu, 2021 ). In order to identify Q-Markers from CMM related preparations, “spider-web” mode was successfully developed and extended to apply in stability study, optimization of extracting methods and processing parameters, screening of active fractions, and so on ( Li et al, 2019b , Wang et al, 2016 , Yang et al, 2018 , Yu et al, 2018 , Zhang et al, 2019a ). “Spider-web” mode based on “content-stability-activity” has been proven to be a great strategy, which can filter out the redundant compounds and focus on the key indexes of quality control ( Zhang et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…have been reported [14][15][16][17]. There is no doubt that a systematic understanding of the stability of bioactive compounds would contribute to improvements in manufacturing and controlling the quality of CMMs [18][19][20]. Meanwhile, it is also vital to design the suitable sample packaging and choose storage conditions for products.…”
Section: Introductionmentioning
confidence: 99%